2016
DOI: 10.1262/jrd.2016-103
|View full text |Cite
|
Sign up to set email alerts
|

Efficient pig ICSI using Percoll-selected spermatozoa; evidence for the essential role of phospholipase C-ζ in ICSI success

Abstract: In pigs, the damaged sperm membrane leads to leakage of phospholipase C-ζ (PLCζ), which has been identified as a sperm factor, and a reduction of oocyte-activating ability. In this study, we investigated whether sperm selected by Percoll gradient centrifugation (Percoll) have sufficient PLCζ, and whether the efficiency of fertilization and blastocyst formation after intracytoplasmic sperm injection (ICSI) using Percoll-selected sperm can be improved. Percoll-selected sperm (Percoll group) or sperm without Perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Indeed, immediately after thawing, more than half of the pig sperm were found to have lost PLCζ immunoreactivity, leading to failure of oocyte activation after ICSI [33]. Use of sperm with appropriate levels of PLCζ for ICSI actually increases the efficiency of oocyte activation and normal fertilization [33]. Our findings suggest that the primary reason for failure of oocyte activation after ICSI may be a deficit, rather than a difference, in the pattern of Ca 2+ oscillation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Indeed, immediately after thawing, more than half of the pig sperm were found to have lost PLCζ immunoreactivity, leading to failure of oocyte activation after ICSI [33]. Use of sperm with appropriate levels of PLCζ for ICSI actually increases the efficiency of oocyte activation and normal fertilization [33]. Our findings suggest that the primary reason for failure of oocyte activation after ICSI may be a deficit, rather than a difference, in the pattern of Ca 2+ oscillation.…”
Section: Discussionmentioning
confidence: 92%
“…The membranes of pig sperm can be damaged during the freezing and thawing processes associated with cryopreservation [32], and such damage can lead to leakage of intracellular PLCζ [29]. Indeed, immediately after thawing, more than half of the pig sperm were found to have lost PLCζ immunoreactivity, leading to failure of oocyte activation after ICSI [33]. Use of sperm with appropriate levels of PLCζ for ICSI actually increases the efficiency of oocyte activation and normal fertilization [33].…”
Section: Discussionmentioning
confidence: 99%
“…The result of a recent study showed that DGC procedure is effective in the separation of spermatozoa with PLCζ, and these spermatozoa result in high oocyte activation after ICSI in pig (Nakai et al, ). Furthermore, Kashir et al () demonstrated that percentage of spermatozoa containing PLCζ was significantly higher following DGC procedure compared to neat semen while cryopreservation of semen has significant detrimental effects upon spermatozoa containing PLCζ.…”
Section: Discussionmentioning
confidence: 99%
“…These decreases in development may be due to selection of damaged sperm and/or incomplete oocyte activation. Importantly, boar sperm selected by a Percoll gradient were shown to have higher abundance of phospholipase C-ζ (PLCζ), a well-studied sperm-borne oocyte activation factor, and the use of Percoll-selected sperm for ICSI increased monospermic fertilization and oocyte activation as well as development to the blastocyst stage [47]. Several protocols use polyvinylpyrrolidone (PVP) for sperm immobilization before ICSI; however, this compound is toxic when injected into oocytes.…”
Section: In Vitro Fertilizationmentioning
confidence: 99%